2022
DOI: 10.31234/osf.io/pb9hn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing acceptance and commitment therapy for adolescent mental health: Single-case A-B design with high temporal density assessments

Abstract: Using a single-case A-B design with high temporal density assessments, the present study examined the impact of a ten-session group-based acceptance and commitment therapy (ACT) intervention on adolescents’ distress, psychological inflexibility, cognitive fusion, generalized pliance, and perceived ply workability. Six participants aged 16 to 19 years were invited to (i) attend a weekly ACT group, submit ecological momentary assessments daily for 69-days, and (iii) complete standardized questionnaires pre- and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…However, our findings also deviate from those of Levin et al (2014), since unlike them, we observed no significant improvements in psychological flexibility post-intervention. Finally, our findings regarding the effects of ACT on pliance and tracking (as per the standardized measures) depart from extant research evidencing that ACT reduces problematic rule-following (Ruiz et al, 2020b;Salazar et al, 2020;Stapleton et al, 2022b).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, our findings also deviate from those of Levin et al (2014), since unlike them, we observed no significant improvements in psychological flexibility post-intervention. Finally, our findings regarding the effects of ACT on pliance and tracking (as per the standardized measures) depart from extant research evidencing that ACT reduces problematic rule-following (Ruiz et al, 2020b;Salazar et al, 2020;Stapleton et al, 2022b).…”
Section: Discussioncontrasting
confidence: 99%
“…Second, the present study is one of few to explicitly target problematic rule-following (Ruiz et al, 2020b;Salazar et al, 2020;Stapleton et al, 2022b), and is the only study to measure both pliance and tracking. Third, we collected both quantitative and qualitative intervention satisfaction data, the latter of which is often overlooked in acceptability trials (Lavelle et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations